An experimental investigation of 1,2-dimethoxy ethane as a fuel additive in biodiesel-fueled diesel engine - Ozturk, Gokhan; Senocak, Safak Melih; Senocak, Nihat; Firat, Mujdat (Elsevier Sci Ltd, 2024)
Recently, researchers have focused on the addition of various additives to biodiesel and other petroleum-derived fuels to improve combustion characteristics and reduce pollutant emissions in internal combustion engines. This study explores the effects of integrating 1,2-dimethoxy ethane (1,2-DME) into reference fuels (RF), including 100 % diesel (D100), 100 % biodiesel (B100), and a blend of 50 % diesel with 50 % biodiesel (B50). In the experiment, 1,2-DME is added at volumes of 5 %, 10 %, and 15 % while engine load is at 25 %, 50 %, and 75 %. In-cylinder pressure and temperature, heat release rate (HRR), knock intensity (RI), combustion duration (CD), ignition delay (ID), brake thermal efficiency (BTE) and pollutant emissions such as carbon monoxide (CO), nitrogen oxides (NOx), hydrocarbon (HC), and smoke opacity are all evaluated. The findings reveal that increasing the 1,2-DME ratio in the reference fuels enhances HRR, in-cylinder pressure, and temperature. Notably, adding 10 % 1,2-DME to D100 at 25 % engine load significantly increases HRR by approximately 28.65 %. Generally, incorporating 1,2-DME reduces ignition delay, shortens ignition duration and intensifies knock (RI). Analysis of pollutant emissions indicates an increase in nitrogen oxide (NOx) emissions but a reductions in carbon monoxide (CO) and hydrocarbon (HC) emissions with 1,2-DME addition. Furthermore, adding 15 % 1,2-DME to D100 at 25 % engine load reduces smoke opacity by 59.2 %. In summary, the significant effects of 1,2-DME on reference fuels indicate its potential as a viable alternative fuel additive.
Keywords: Biodiesel; Combustion; Emissions; Diesel engines; 1,2-Dimethoxy ethane